Navigating the risks: a systematic review of immune checkpoint inhibitor therapy before liver transplant for hepatocellular carcinoma and its impact on allograft rejection and survival outcomes - Liu, Donghua; Wang, Xinyi; Liu, Xuelian; Li, Jing (Frontiers in Oncology, 2025)
BackgroundThe administration of immune checkpoint inhibitors (ICIs) prior to liver transplantation (LT) for hepatocellular carcinoma (HCC) has been reported. Several studies suggest that ICIs may elevate the risk of allograft rejection (AR) and influence other clinical outcomes. This meta-analysis aimed to assess the efficacy and safety of pre-LT ICI treatment in HCC patients.MethodsA systematic literature search was conducted in PubMed, Embase, Cochrane, and Web of Science for retrospective studies and randomized controlled trials (RCTs) examining pre-LT ICI therapies in HCC patients. Random-effects models were employed to evaluate treatment effects on allograft rejection (AR), complete recovery rate among patients with AR, graft loss, HCC recurrence, and progression-free survival (PFS). Common-effects models were used to assess overall mortality and AR-related mortality. Study quality was evaluated using the JBI critical appraisal tools. The review was registered with PROSPERO (CRD42024616267).ResultsStudies involving HCC patients receiving pre-LT ICIs for downstaging or bridging were included. After screening databases from inception to 31 December 2024, eight studies (n = 229 patients) were included. The studies had diverse designs and were primarily from China and the US. The pooled post-LT AR rate across all eight studies was 19% (95% CI: 12%–30%). The incidence of AR was 24% in the PD-L1 inhibitor group, 18% in the PD-1 inhibitor group, and 20% in the bispecific/combination therapies group. The complete recovery rate among patients with AR was 78% (95% CI: 59%–97%), and graft loss occurred in 4% (95% CI: 1%–7%). The HCC recurrence rate across six studies was 24% (95% CI: 12%–36%). The pooled median recurrence-free survival (RFS) was 17.63 months (95% CI: 11.57–23.69 months). Overall mortality was 8% (95% CI: 4%–12%), and AR-related mortality was 2% (95% CI: 0%–5%). Sensitivity analysis supported the robustness of the results, while funnel plots indicated potential publication bias for several outcomes. This meta-analysis offers a comprehensive synthesis of the impact of pre-LT ICIs on post-transplantation outcomes.ConclusionThe use of ICIs as bridging or downstaging therapy prior to liver transplantation in HCC patients appears feasible.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024616267.